The effect of the mind mapping learning model on the creative thinking ability of elementary students in learning mathematics - Ulfah, Siti Maria; Pahmi, Samsul; Hopeman, Teofilus Ardian; Vladimirovna, Kornienko Elena (Universitas Sarjanawiyata Tamansiswa, 2024)
The primary objective of this study was to explore how the Mind Mapping instructional approach influences the creative thinking abilities of fourth-grade students in mathematics. This research utilized a quantitative method employing a quasi-experimental design involving two distinct groups: one serving as the experimental group and the other as the control group. The study was conducted at SDN Karadenan, with a sample of 24 fourth-grade students participating in the experimental group and 29 students from SDN Paledang in the control group, selected through purposive sampling. The main focus was to assess the impact of the Mind Mapping approach on students' creative thinking skills in mathematics. Data was collected using the t-test method. The mean difference between the two groups was 4.89 (experimental group = 66.70 and control group = 52.65), indicating that the Mind Mapping approach was more effective compared to traditional lecture methods, question-answer sessions, and assignments. The findings were statistically significant (p = 0.000) based on Independent Sample T-Test analysis. As the significance level (0.000) was less than 0.05, the null hypothesis was rejected, confirming that the Mind Mapping approach significantly enhances creative thinking skills in mathematics among students. Thus, it can be concluded that the Mind Mapping instructional model has a substantial positive impact on students' creative thinking abilities in the context of mathematics.